Clinical Implications of ESR1 Mutations in Hormone Receptor-Positive Advanced Breast Cancer - Reinert, Tomas; Saad, Everardo D.; Barrios, Carlos H.; Bines, José (Frontiers in Oncology, 2017)
Hormone receptor (HR) positive breast cancer is the most frequent breast cancer subtype. Endocrine therapy targeting the estrogen receptor (ER) pathway represents the main initial therapeutic approach. The major strategies include estrogen deprivation and the use of selective estrogen modulators or degraders; which show efficacy in the management of metastatic and early stage disease. However, clinical resistance associated with progression of disease remains a significant therapeutic challenge. Mutations of the ESR1 gene, which encodes the ER, have been increasingly recognized as an important mechanism of endocrine therapy resistance, with a prevalence that ranges from 11 to 39%. The majority of these mutations are located within the ligand-binding domain and result in an estrogen-independent constitutive activation of the ER and therefore resistance to estrogen deprivation therapy such as aromatase inhibition. ESR1 mutations, most often detected from liquid biopsies, have been consistently associated with a worse outcome and are being currently evaluated as a potential biomarker to guide therapeutic decisions. At the same time, targeted therapy directed to ESR1-mutated clones is an appealing concept with preclinical and clinical work in progress.